Diversity of vascular flora in Cho Moi and Bach Thong districts, Bac Kan province, Vietnam - Thuy Hang, Hoang Thi; Ly, Tran Dinh (Academia Journal of Biology, 2013)
Using the methods of line survey and standard plot survey to make out the version plots to investigate, classify, and collecte 283 species of vegetation of 138 branches with 87 families, which belonged to 3 types: Polypodiophyta, Gymnospermae and Angiospermae among various living vegetation in Bac Kan province. The result also show that the forest vegetation in Bac Kan province has the follwing most diverse families: Poaceae, Rubiaceae, Moraceae, Euphorbiaceae, Asteraceae and Caesalpiniaceae. Such the plants as Amomum xanthioides, Styrax tonkinensis, Canthium dicoccum var. rostratum, Prunus arborea, Mangietia fordiana.... were often exploited and regularly used. Of the total, 6 rare and precious species are observed in the Red Data Book of Vietnam, and of those species 1 species was as endangered (EN): Madhuca pasquieri; 5 species as vulnerable (VU): Dipterocarpus retusus, Michelia balanse, Aglaia spectabilis, Ardisia silvestris and Canthium dicoccum. It is necessary that Bac Kan authority should set up systematic solutions in technique, policy, and management in order to preserve and regenerate the plant cover, especially the rare species.